Effect of Substituents on Kinetics of Phenols by Pyridinium Fluorochromate in Glacial Acetic Acid - Patil, S.G.; Joshi, S.B. (Asian Journal of Chemistry, 2010)
The effect of substituents on the reaction rate for oxidation of phenol by pyridinium fluorochromate has been investigated in glacial acetic acid at 303 and 308 K by ploting log k2 vs. 6x. From the slope of the resulting straight line, the values of ‘ρ’ were calculated. The negative ‘ρ’ values in the reaction indicating the development of +ve charge at the reaction. The reaction is thus accelerated by electron donating substituents, which help to delocalize the +ve charge in the intermediate complex and correspondingly retarted by electron-withdrawing substituents. The Hammett treatment has been applied to these reactions and to different functional groups.